1988
DOI: 10.1073/pnas.85.21.7849
|View full text |Cite
|
Sign up to set email alerts
|

Functional reconstitution of a proton-translocating system responsive to fusicoccin.

Abstract: Crude fusicoccin binding proteins and a partially purified plasma membrane H+-transporting ATPase (EC 3.6.1.34), both solubilized from maize tissues, were simultaneously inserted into liposomes by the freeze-thaw method. ATP-driven intravesicular acidification in the proteoliposomes, measured by the fluorescence quenching of the dye 9-amino-6-chloro-2-methoxyacridine, markedly increased upon addition of fusicoccin to the reconstituted system. This effect could not be observed when binding sites and ATPase prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

1991
1991
1997
1997

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…The physiological factors regulating the activity of plant ATPase are not so well characterized as in the case of the yeast enzyme. Activation by the phytotoxin, fusicoccin, has recently been reconstituted with partially purified preparations of ATPase and fusicoccin receptor [24,25]. Light effects on the enzyme seem to be mediated by calcium-calmodulin protein kinases [26] and phosphoinositide changes [27].…”
Section: Auto-inhibitory Domain At the C-ter-minus Of Yeast And Plantmentioning
confidence: 99%
“…The physiological factors regulating the activity of plant ATPase are not so well characterized as in the case of the yeast enzyme. Activation by the phytotoxin, fusicoccin, has recently been reconstituted with partially purified preparations of ATPase and fusicoccin receptor [24,25]. Light effects on the enzyme seem to be mediated by calcium-calmodulin protein kinases [26] and phosphoinositide changes [27].…”
Section: Auto-inhibitory Domain At the C-ter-minus Of Yeast And Plantmentioning
confidence: 99%
“…(Ballio et al, 1964), interacts with high affinity and specificity to binding proteins localized at the plasma membrane of plant cells (Dohrmann et al, 1977;Ballio et al, 1980;Pesci et al, 1979a). Although evidence obtained in vitro in different systems (Rasi-Caldogno et al, 1986;Aducci et al, 1988;Blum et al, 1988;Marra et al, 1992) prove that the ultimate target of FC action is the H+-ATPase, the molecular mechanism of this activation is not understood.…”
mentioning
confidence: 99%
“…Work on isolated PM vesicles as well as on proteoliposomes reconstituted with purified PM H+-ATPase and crude or partially purified FCBP has shown that FC binding to the FCBP leads to the activation of the PM HtATPase (Rasi-Caldogno and Pugliarello, 1985;Rasi-Caldogno et al, 1986Aducci et al, 1988;Blum et al, 1988;De Miclielis et al, 1988a, 198813, 1989a, 1989bMarra et al, 1992;Olivari et al, 1993). At least in native PM vesicles this activation determines a shift of the pH optimum of the enzyme toward more alkaline values and a decrease of the apparent K, for MgATP (Rasi-Caldogno et al, 1986De Michelis et al, 1991;Johansson et al, 1993;Lanfermeijer and Prins, 1994).…”
mentioning
confidence: 99%